(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Description of clinical findings, laboratory testing and epidemiology of patients with NTM pulmonary disease at the National Lung Hospital from 2017-2021. Methods: Cross-sectional study on 136 patients diagnosed with NTM-PD at National Lung Hospital from 1/2017 to 6/2021. Results: The average age of 136 patients was 58.2 ± 15.4 years old, the patients more than 60 years old accounted for the highest rate of 44.1%. The proportion of M.abscessus, M.intracellulare and M.avium were 45,45%, 35,66% and 11,19%, respectively. 40% patients had previous TB treatment. 16% patients had diseases related to lung structure (COPD, bronchiectasis). The major of patients are detected 2-4 months from the time of admission to the time of confirmed diagnosis. Cough with production more than 2 weeks is most common (>90%). 50.7% of cases had smear positive. Nodular and bronchiectasis on chest CT were more common in MAC-PD patients (61.2%) than in M. abscessus-PD ones (47.7%) (p<0.05). Cavitary on chest CT were higher in M. abscessus -PD patients (9.2%) than MAC-PD patients (3.0%) (p>0.05). Conclusion: The clinical symptoms of NTM-PD are diverse, variable and non-specific because they can appear in many different respiratory diseases.